Kebijakan Pemberian Bantuan Perguruan Tinggi Keagamaan Islam Negeri dan Swasta - Khoirunnisaa’ . (TABYIN: JURNAL PENDIDIKAN ISLAM, 2022)
The difference in the allocation of aid from the government between State Islamic Religious Higher Education (PTKIN) and Private Islamic Religious Higher Education (PTKIS) is due to the difference in the implementation of education. The organizers are the government, while the PTKIS organizers are organizations or foundations. However, the direction and policy of developing higher education based on Islam is an effort to improve the quality of education and institutions that focus on 4 (four) aspects, namely increasing access to higher education, improving the quality of PTKI services, improving the quality of lecturers, productivity and innovation of PTKI. One of the program target indicators is the indicator for the number of professional lecturers at PTKI: Target Indicators for the 2015 Target Program, the proportion of qualified lecturers at least S2 is 82.5%, S3 12.0% and the 2019 target is the proportion of lecturers with a minimum qualification of S3 20.0%. 2%. Funding for Islamic Education is the joint responsibility of the government, local government and the community. The increase in Islamic education is carried out through a significant increase in the budget so that it reaches 25.12% of the 2019 State Budget. The average budget projection has increased between 5-6% per year